PEMODELAN SAMBUNGAN LAS PADA STRUKTUR BALOK KOLOM BAJA BERBASIS PROGRAM ELEMEN HINGGA - Gati Annisa Hayu; Machmud Budi Sulistyo (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2021)
In steel construction the selection of types and installation details of connection is an important thing that cannot be ignored. There are three types of steel connections, namely bolts, welds, and rivets. Welding connections have a good strength if conducted in proper quality control. In addition, these connections are also inexpensive and easy to implement. The focus of this study is the modelling of welding connections which can produce outputs that are close to the experimental results. The modelling is done by using finite element program. There are two models carried out; Model-1 uses tie constraint interaction type, meanwhile Model-2 uses merge and chamfer type. Results show that Model-2 is closer to the experimental result with an accuracy of 97.75% for its ultimate load. The deformation that occurred in Model-2 also resembles the experiment deformation. In terms of energy dissipation, the experimental result is 78,036.396 kN.mm while the result of Model-2 is 94,456.982 kN.mm. Thus, the accuracy level of Model-2 is 82.62%.